Top responsiveness and stable partitions in coalition formation games - Dinko Dimitrov; Shao Chin Sung (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
Top responsiveness is introduced by Alcalde and Revilla [Journal of Mathematical Economics 40 (2004) 869-887] as a property which induces a rich domain on players's preferences in hedonic games, and guarantees the existence of core stable partitions. We strengthen this observation by proving the existence of strict core stable partitions, and when a mutuality condition is imposed as well, the existence of Nash stable partitions.
urn:nbn:de:hbz:361-6667
Keywords: C71; C72; C78; D71; 330; Coalition formation; Nash stability; Partitions; Strict core stability